Rotational quantum beat lasing without inversion - Richter, Maria; Lytova, Marianna; Morales, Felipe; Haessler, Stefan; Smirnova, Olga; Spanner, Michael; Ivanov, Misha (Optics InfoBase Conference Papers, 2020)
We show that lasing without inversion arises naturally during propagation of intense femtosecond laser pulses in air. It is triggered by the combination of molecular ionization and molecular alignment, both unavoidable in intense light fields.
CRIS-Team Scopus Importer:2023-04-20